Identification of genes expressed by immune cells of the colon that are regulated by colorectal cancer‐associated variants. Issue 10 (13th November 2013) - Peltekova, Vanya D.; Lemire, Mathieu; Qazi, Aamer M.; Zaidi, Syed H. E.; Trinh, Quang M.; Bielecki, Ryszard; Rogers, Marianne; Hodgson, Lyndsey; Wang, Mike; D'Souza, David J. A.; Zandi, Sasan; Chong, Taryne; et al.
<x xml:space="preserve">Abstract</x> A locus on human chromosome 11q23 tagged by marker rs3802842 was associated with colorectal cancer (CRC) in a genome‐wide association study; this finding has been replicated in case–control studies worldwide. In order to identify biologic factors at this locus that are related to the etiopathology of CRC, we used microarray‐based target selection methods, coupled to next‐generation sequencing, to study 103 kb at the 11q23 locus. We genotyped 369 putative variants from 1, 030 patients with CRC (cases) and 1, 061 individuals without CRC (controls) from the Ontario Familial Colorectal Cancer Registry. Two previously uncharacterized genes, COLCA1 and COLCA2, were found to be co‐regulated genes that are transcribed from opposite strands. Expression levels of COLCA1 and COLCA2 transcripts correlate with rs3802842 genotypes. In colon tissues, COLCA1 co‐localizes with crystalloid granules of eosinophils and granular organelles of mast cells, neutrophils, macrophages, dendritic cells and differentiated myeloid‐derived cell lines. COLCA2 is present in the cytoplasm of normal epithelial, immune and other cell lineages, as well as tumor cells. Tissue microarray analysis demonstrates the association of rs3802842 with lymphocyte density in the lamina propria (p = 0.014) and levels of COLCA1 in the lamina propria (p = 0.00016) and COLCA2 (tumor cells, p = 0.0041 and lamina propria, p = 6 × 10–5). In conclusion, genetic, expression and immunohistochemical data implicate COLCA1 and COLCA2 in the pathogenesis of colon cancer. Histologic analyses indicate the involvement of immune pathways.